2021
DOI: 10.3390/ma14102616
|View full text |Cite
|
Sign up to set email alerts
|

New-Generation Liquid Crystal Materials for Application in Infrared Region

Abstract: This study presents 13 new organic compounds with self-assembling behavior, which can be divided into two groups. The first synthesized group includes compounds based on 4′-(trifluoromethoxy)-[1,1′-biphenyl]-4-yl-4-(trifluoromethoxy) benzoate core, and the second includes compounds based on 4-((4-(trifluoromethoxy)phenyl)ethynyl)phenyl-4-(trifluoromethoxy) benzoate core. They differ in the number and location of the fluorine atom in the lateral position. Mesomorphic properties, phase transition enthalpies, ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Saccone et al suggested that on changing the degree of fluorination, the fine tuning of temperature is possible over a mesomorphic range [23]. Phillips and Pombeiro, and others have reported that the addition of halogen atom in a drug molecule may increase its liophilicity and also the addition of halogen atom induces strong dipole moment within the liquid crystal and these results in the enhancement of lattice stability [24][25][26][27]. This also increases the ionic radius of the molecule and makes it more parallel in the alignment within an electrode [28].…”
Section: Introductionmentioning
confidence: 99%
“…Saccone et al suggested that on changing the degree of fluorination, the fine tuning of temperature is possible over a mesomorphic range [23]. Phillips and Pombeiro, and others have reported that the addition of halogen atom in a drug molecule may increase its liophilicity and also the addition of halogen atom induces strong dipole moment within the liquid crystal and these results in the enhancement of lattice stability [24][25][26][27]. This also increases the ionic radius of the molecule and makes it more parallel in the alignment within an electrode [28].…”
Section: Introductionmentioning
confidence: 99%
“…The intense peak at 1230 cm –1 represents the stretching vibration from the C–O bonds in the ester and ether functional groups. Similarly, the presence of a fluorine atom in the CQD has been evidenced by the strong C–F stretching vibrations in the range 1015 to 1150 cm –1 . , All these observations confirm CQDs with an sp 2 -hybridized aromatic nucleus bearing abundant ester, ether, alkyl, and hydroxyl functional groups, which explains the organophilic nature of CQDs . This also might account for its high compatibility in different LCs.…”
Section: Resultsmentioning
confidence: 66%
“…Other applications requiring this property are lower frequencies of the electromagnetic spectrum (from infrared down to THz and GHz), as the optical phase shift produced by the LC is directly proportional to its birefringence and the working frequency. For example, they have been proposed as active medium in metamaterials and metasurfaces 5 , 6 , THz 7 9 , GHz 10 , 11 and infrared devices 12 .…”
Section: Introductionmentioning
confidence: 99%